Error analysis for an ALE evolving surface finite element method. Issue 2 (30th October 2014) - Elliott, Charles M.; Venkataraman, Chandrasekhar
<x xml:space="preserve">Abstract</x> We consider an arbitrary Lagrangian–Eulerian evolving surface finite element method for the numerical approximation of advection and diffusion of a conserved scalar quantity on a moving surface. We describe the method, prove optimal order error bounds and present numerical simulations that agree with the theoretical results. © 2014 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq 31: 459–499, 2015